2011
DOI: 10.3113/fai.2011.0802
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological Evaluation of Diabetic and Non-Diabetic Plantar Soft Tissue

Abstract: Background Diabetic foot ulceration has a complex and multi-factorial etiology and can involve changes in the pathophysiology of the plantar soft tissue. In the current study, histomorphological analyses of diabetic and non-diabetic plantar tissue were performed. It was hypothesized that the diabetic tissue would have thicker skin (epidermis and dermis), less interdigitation between the dermis and epidermis, thicker elastic septa and decreased adipose cell size. Materials and Methods Two locations of the foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 44 publications
9
43
0
1
Order By: Relevance
“…The PFP is often involved in complications of the diabetic foot. Interestingly, it appears that the thickness of the elastic septa and the dermis are increased in diabetic PFP (Wang et al 2011). Thinning of the epidermis and stiffening of plantar soft tissues in diabetic PFP increase the risk of tissue breakdown and ulcer formation (Chao et al 2011).…”
Section: A B C Dmentioning
confidence: 99%
See 2 more Smart Citations
“…The PFP is often involved in complications of the diabetic foot. Interestingly, it appears that the thickness of the elastic septa and the dermis are increased in diabetic PFP (Wang et al 2011). Thinning of the epidermis and stiffening of plantar soft tissues in diabetic PFP increase the risk of tissue breakdown and ulcer formation (Chao et al 2011).…”
Section: A B C Dmentioning
confidence: 99%
“…This difference may well characterize FPU in aging, but it does not represent a reduction of the total number of adipocytes in the PFP. Studies on the diabetic PFP have found that the total number of adipocytes remains unchanged but the volume of adipocytes may or may not be reduced (Waldecker, 2001;Wang et al 2011). The FPU was featured as a collection of adipocyte clusters and a neurovascular bundle encased by an elastic septum.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are particularly important with regard to ulceration of plantar foot tissues. One documented pathological change is increased thickness of the elastic septa (Jahss et al 1992, Buschmann et al 1995, Wang et al 2010). Although ideally all tissue used in a given study would be fixed in the same way, sometimes this is not possible.…”
mentioning
confidence: 99%
“…An understanding of the diseaseinduced tissue property changes that contribute to plantar ulceration requires first quantifying these changes under relevant plantar loading, i.e., compression and shear. Towards this goal, our group has evaluated diabetic changes in the compressive [2,3] and histomorphological [4] properties of the plantar soft tissue. We also recently obtained the corresponding shear properties from the specimens previously tested in compression [5].…”
Section: Introductionmentioning
confidence: 99%